2010
DOI: 10.1002/hipo.20868
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hippocampal high‐frequency electrical stimulation in memory formation and their association with amino acid tissue content and release in normal rats

Abstract: Hippocampal high frequency electrical stimulation (HFS) at 130 Hz has been proposed as a therapeutical strategy to control neurological disorders such as intractable temporal lobe epilepsy (TLE). This study was carried out to determine the effects of hippocampal HFS on the memory process and the probable involvement of amino acids. Using the autoshaping task, we found that animals receiving hippocampal HFS showed augmented short-term, but not long-term memory formation, an effect blocked by bicuculline pretrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 52 publications
2
14
0
Order By: Relevance
“…An increase in the extracellular glycine concentration measured by microdialysis has been described in the substantia nigra pars compacta of the rat following calciumdependent high potassium-mediated depolarization [106]), as well as following the application of high-frequency electrical stimulations in the hippocampus [112]. These experiments suggest that the fluctuations of the extracellular levels of glycine in these areas depend on the electrical activity of the network and could be calcium-dependent.…”
Section: Glycinementioning
confidence: 90%
See 1 more Smart Citation
“…An increase in the extracellular glycine concentration measured by microdialysis has been described in the substantia nigra pars compacta of the rat following calciumdependent high potassium-mediated depolarization [106]), as well as following the application of high-frequency electrical stimulations in the hippocampus [112]. These experiments suggest that the fluctuations of the extracellular levels of glycine in these areas depend on the electrical activity of the network and could be calcium-dependent.…”
Section: Glycinementioning
confidence: 90%
“…The hypothesis of the presence of a significant amount of glycine in the extracellular space was strengthened by data showing that a proportion of strychnine-sensitive GlyRs are continuously active in resting CA1 pyramidal neurons of the hippocampus, creating a state of tonic inhibition that "shunts" EPSPs evoked by shocking the Schaffer collaterals [111]. Finally, microdialysis experiments also revealed a functionally significant extracellular concentration of glycine in the hippocampus during high-frequency electrical stimulations [112]. There is also evidence that Bergmann glia can release glycine [113], and we recently showed that radial cells in the embryonic spinal cord can release glycine as well, thereby modulating the early electrical activity of the developing neuronal network [9].…”
Section: Glycinementioning
confidence: 99%
“…However, a different optogenetic strategy for seizure suppression that mimics electrical HFS protocols by activating neurons can also effective. Electrical HFS has been thought to suppress seizures by generating a depolarization block related to the inactivation of sodium channels (10, 11) or driving GABA release during stimulation (24, 25). In the present study, histological analyses show that mostly interneurons express ChR2 in the Thy1-ChR2 mice and thus GABA release could be enhanced by optical stimulation together with the activation of some pyramidal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, stimulation of the entorhinal region was found to enhance memory for spatial information when applied during learning [6]. In animal studies, high frequency stimulation activates specific amino acids in the hippocampus that may be involved in the enhancement of short-term memory formation [7]. Also, formation of water maze memory is facilitated after bilateral stimulation of the entorhinal cortex [8].…”
Section: Introductionmentioning
confidence: 99%